2022
DOI: 10.7759/cureus.27120
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Inequality in Survival Outcomes of Women With Triple Negative Breast Cancer

Abstract: Triple-negative breast cancer (TNBC) is the most lethal group of breast cancers. Socioeconomic factors may contribute to differences in survival rates. This study aims to identify racial/ethnic disparities in five-year survival rates among women affected by TNBC in the United States. MethodsThis retrospective study analyzed data from the 2010-2016 Surveillance, Epidemiology, and End Results Program database. Patients with a primary malignancy of triple-negative breast cancer were included in this study. Cancer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…This study reported that higher proportion of TNBC tumors in postmenopausal patients and their association with favourable tumor characteristics and better DFS compared to premenopausal patients [29] which is contrary to our observations. Disparities in TNBC outcomes have been reported based on race and ethnicity in multiple studies earlier [30][31][32]. Younger median age of our cohort and ethnicity-based differences between Indian and Japanese women might have contributed to the observed difference.…”
Section: Discussionmentioning
confidence: 57%
“…This study reported that higher proportion of TNBC tumors in postmenopausal patients and their association with favourable tumor characteristics and better DFS compared to premenopausal patients [29] which is contrary to our observations. Disparities in TNBC outcomes have been reported based on race and ethnicity in multiple studies earlier [30][31][32]. Younger median age of our cohort and ethnicity-based differences between Indian and Japanese women might have contributed to the observed difference.…”
Section: Discussionmentioning
confidence: 57%
“…This study reported that higher proportion of TNBC tumors in postmenopausal patients and their association with favourable tumor characteristics and better DFS compared to premenopausal patients 31 which is contrary to our observations. Disparities in TNBC outcomes have been reported based on race and ethnicity in multiple studies earlier [32][33][34] . Younger median age of our cohort and ethnicity-based differences between Indian and Japanese women might have contributed to the observed difference.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to evidence-based management improves outcomes in patients with breast cancer [7,8]. A few studies have looked at disparities in treatment and outcomes in triple-negative breast cancer patients [9,10]. However, the available studies did not design a treatment algorithm based on GAC by cancer stage.…”
Section: Introductionmentioning
confidence: 99%